Envi ronmental Impact of Oil Exploration on the Crustacean Zooplankton of Osse River, Southern Nigeria - Ogbeibu’i, Anthony E.; Omoigberalc, Michael O. (Biological Sciences - PJSIR, 2007)
. Th e i mpact of crude oi l expl or ation on the cru stacean zoopl an kton of Osse R i ver, Edo State (N i ger i a) was i n vesti gated at fi ve si tes between J ul y 2000 and Ju n e 2002. Cl adocera accoun ted for 60.85% of th e tota l n umber of organ i sm s col l ected from a l l th e fi ve stat i ons, wh i l e Copepoda con tri but ed 39. 1 5%. Ch ydor i dae, th e on l y c l adoceran fami l y was represented by II tax a of two su b fomi l i c ·, A l oni n ae (7) an d Ch yd or i n ae (4) . Th e overa l l abu nd an ce of Cladoccra was si g n i fi can t l y d i ffer cnt (P < 0.05) amo n g t h e st a t. i on s. A 11osl er ior i Du n cun M u l t i p l e Ran ge (DM R ) t.c:t sh owed tha t t h e a bu n d an ce o r l adocera wu s si gn i ri can t. J y h i gh er ( P < 0.05) i n 3 sta t i on s, wh ereas, aper od abu n d an ce wa s ·i gn i f’i ea ntl y h i oh er ( P < 0.05) i n 2 sta t i on s. Th e d i versity i n d i ces rev ea l ed t h e h i gh est an d th e l owest ta xa r i ch n ess, wh i l e ’ h an n n - W i cn cr ,rn d Eve n n ess i nd i ces were h i h er i n 3 st a ti on s. Th e tem pornl d y n am i cs revea l ed h i gh er fau n a ] abu n da n ce d u ri n g t.h e d ry season .